Circumcision related to urinary tract infections, sexually transmitted infections, human immunodeficiency virus infections, and penile and cervical cancer. (9th April 2013) - Hayashi, Yutaro; Kohri, Kenjiro
Abstract: Male circumcision has been carried out as a prophylactic measure against future diseases, as well as a rite of passage due to religious practice and definite medical indication. The present review discusses the benefits of male circumcision on the prevention of urinary tract infections, and the importance of circumcision in congenital urinary system anomalies, such as vesicoureteral reflux. Additionally the present review examines the associations between circumcision and sexually transmitted infections, including human immunodeficiency virus, and the preventive effect of circumcision on penile cancer and cervical cancer of female partners.